2014
DOI: 10.1589/jpts.26.825
|View full text |Cite
|
Sign up to set email alerts
|

Tai Chi Improves Oxidative Stress Response and DNA Damage/Repair in Young Sedentary Females

Abstract: [Purpose] This study was to examine the effects of 12 weeks of Tai Chi (TC) exercise on antioxidant capacity, and DNA damage/repair in young females who did not perform regular physical exercise. [Subjects and Methods] Ten female students from a Chinese university voluntarily participated in this program. All of them practiced the 24-form simplified Tai Chi, 5 times weekly, for 12 weeks. Plasma levels of superoxide dismutase (SOD), glutathione peroxidase (GPx), malondialdehyde (MDA), glutathione (GSH), hydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
(35 reference statements)
2
12
0
1
Order By: Relevance
“…These findings were in agreement with several previous studies (Goon et al, 2009;Huang et al, 2014;Onur et al, 2011;Wadiah et al, 2015). Huang et al (2014) reported that there was no significant change in GPx level at week 8 but there was a significant increase in GPx activity at week 12. Similarly, Goon et al (2009) reported that there was no significant increase in SOD level at month 6 but there was a significant increase in SOD activity at month 12.…”
supporting
confidence: 94%
See 1 more Smart Citation
“…These findings were in agreement with several previous studies (Goon et al, 2009;Huang et al, 2014;Onur et al, 2011;Wadiah et al, 2015). Huang et al (2014) reported that there was no significant change in GPx level at week 8 but there was a significant increase in GPx activity at week 12. Similarly, Goon et al (2009) reported that there was no significant increase in SOD level at month 6 but there was a significant increase in SOD activity at month 12.…”
supporting
confidence: 94%
“…The response to increased oxidative stress is associated with the upregulation of the various antioxidant activities in the body including the endogeneous antioxidant enzymes such as SOD, GPx and CAT (Cheeseman & Slater, 1993). Even though we did not measure oxidative stress levels, the increased trend in SOD and GPx in the J group in this study reflects that there might be an increase in oxidative stress following regular jogging exercise for 8 weeks (Goon et al, 2009;Huang et al, 2014). It has also been shown that both high intensity and endurance training upregulate antioxidant enzyme activities in response to chronic exposure to oxidants during regular exercise training (Criswell et al, 1993;.…”
mentioning
confidence: 78%
“…Regarding the specific literature, a few studies have been made in humans. Huang et al (Huang et al 2014) observed no changes in plasma 8-OHdG and a significant increase in plasma OGG1 level after 12 weeks of Tai-Chi exercise practice of light intensity (54.3-57.1 % of maximum HR). These results are somewhat confusing since OGG1 is a DNA nuclease located in cell nuclei, and the analyses were performed in plasma.…”
Section: Discussionmentioning
confidence: 66%
“…It is well known that many kinds of exhaustive high-intensity endurance exercises cause DNA damage but that those exercises that do not cause a high level of stress in the body, such as habitual exercise or low- or moderate-intensity exercise, do not cause DNA damage 8 , 22 ) . In the present study, although the 42 km marathon group showed a higher value for tail moment than the other groups, relatively short distance (10 km and 21 km) marathons were also shown to cause DNA damage.…”
Section: Discussionmentioning
confidence: 99%